Analysis and trends of caesarean sections using Robson’s classification over 7-year period at a rural teaching hospital - Mahathi Nadella; Shyam S. Maila; Indira Nagelli; Kalpana Basany (Journal of Family Medicine and Primary Care)
Background: A ten-group classification system of caesarean section was proposed by Michael Robson in 2001. It is helpful in comparing the rates of caesarean section between hospitals. The objective of this study was to determine the caesarean section rates to analyse trends of caesarean section and classify according to Robson’s categories. Methods: This cross-sectional study was conducted from 2016 to 2022. A total of 3176 women who underwent caesarean section were grouped under Robson’s ten-group classification system. Results: The most common group was Group 5 (All multiparous women with at least one previous uterine scar, with single cephalic pregnancy, ≥37 weeks gestation) followed by Group 2 (Nulliparous women, with single cephalic pregnancy, >37 weeks gestation who either had labour induced or were delivered by caesarean section before labour). Results were obtained for the specified period (from 2016 to 2022), and Group 5 contributes more to the total CS rates (45% in 2016, 46% in 2017, 46% in 2018, 57% in 2019, 49% in 2020, 52% in 2021, 54% in 2022), followed by Group 2 (20% in 2016, 17% in 2017, 18% in 2018, 19% in 2019, 26% in 2020, 24% in 2021, 24% in 2022). Conclusion: Pregnant women with prior uterine scars contribute more to caesarean section rates according to Robson’s categories. Hence, strategies must be implemented to lower the primary caesarean section rates.